A framework of influencing factors for successful disaster management in United Arab Emirates (UAE) - Mohamed Alfzari, Saeed Mohamed Khalfan (2022)
The United Arab Emirates (UAE) is a wealthy country that has an excellent opportunity to strengthen its emergency management system using its financial resources. However, the government needs to focus on improvements require solutions of disastrous issues rather than economic improvement. This study seeks to address the influencing factors that significantly affect disaster management in UAE. This study’s efforts are geared towards consciously evolving a contemporary development style and culture, as well as institutionalising its operational procedures, in such a way that reconfigures the current development framework into a privilege framework. Therefore, the purpose of this study to develop a framework for factors influencing successful disaster management in UAE. The objectives of this study are to identify influential factors and their impact on disaster prevalence reduction and successful disaster management in the UAE. A total of 269 questionnaires were collected from experts involved in disaster management using questionnaires. The Analysis of Moment Structures Equation Modelling (AMOS-SEM) model was developed based on groups related to disaster management functions (institutional factors, environmental factors, human factors, and natural factors) and people’s participation in the development. The findings indicated that the influencing factors effected significantly the successful disaster management and reduced disaster prevalence. This research could further strengthen structures and create a new output, an adoptable emergency management tool. In conclusion, it is hoped that the framework developed can assist in successful disaster management to reduce natural disasters in the UAE.